ANALISIS PERBEDAAN SIKAP IBU HAMIL YANG DIVKASIN DAN TIDAK DIVAKSIN COVID-19 DI PUSKESMAS SIMPUR KOTA BANDAR LAMPUNG TAHUN 2021 - Fonda Octarianingsih Shariff; Festy Ladyani Mustofa; Devita Febriani Putri; Renaldy Firdaus (Medula, 2022)
Coronavirus Disease 2019 or also called COVID-19 is an infectious disease, caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). SARS-CoV-2 is a new type of coronavirus that has never been identified before in humans. COVID-19 vaccination aims to reduce the transmission of COVID-19 transmission, reduce the number of pain and death due to COVID-19, achieve herd immunity and protect pregnant women to remain socially and economically productive. Knowing the differences in attitudes of pregnant women who are vaccinated and non vaccinated for COVID-19 at public health center simpur Bandar Lampung city in 2021. Design methods used are descriptive analytics with a Case Control approach. Sampling technique with Quota Sampling research technique. The results showed from a sample of 30 that pregnant women who had done the vaccine, with a good attitude as much as 14 (46.7%), and with a bad attitude as much as 1 person (3.3%). While pregnant women who do not vaccinate with good attitudes as much as 2 (6.7%), and with bad attitudes as many as 13 people (43.3%). Based on differences in attitudes of pregnant women that the number of attitudes of pregnant women who have been vaccinated as many as 15 people and the number of pregnant women who are not vaccinated as many as 15 people. After the T-TEST test, the attitude of pregnant women who have been vaccinated and the attitude of pregnant women who are not vaccinated get a result of p value = 0.000 this means that H1 is accepted and H0 is rejected where there is a significant difference  in the attitude of vaccinated pregnant women and the attitudes of pregnant women who are non vaccinated for COVID-19. There is a difference in the attitude of pregnant women who are vaccinated and not vaccinated against COVID-19 at the Simpur Health Center in Bandar Lampung City in 2021 with a signification level of 0.000 obtained by P<0.05